Longitudinal study of daily variation of rats' behavior in the elevated plus-maze - Andrade, MMM; Tome, M. F.; Santiago, E. S.; Lucia-Santos, A.; de Andrade, TGCS (Elsevier B.V., 2003)
We conducted a longitudinal study about daily variation of Wistar male rats' behavior in the elevated plus-maze (EPM) evaluated in the 1st, 2nd, 3rd, 6th, 12th, and 18th months of life. Animals were submitted to the plus-maze in 12 sessions at 2-h intervals (n=72, 6 per time point). Spontaneous rest-activity rhythm of four animals was assessed by observation of 24-h videotape records. Time series were analyzed by Cosinor method. Behavioral rates on the six occasions and in light and dark phases were compared by means of two-way ANOVA with repeated measures. Exploratory behavior in EPM was smaller in the light phase and in older animals. Higher values of open and closed arms exploration were observed in the first and third months of the dark phase, and in the first month of the light phase. Adjustment to the 24-h period was significant at all stages for rest-activity data, number of entries in closed arms, and time on center, and for three to five stages for open-arm exploration. In general, 24 h variability was more pronounced in younger animals compared with older ones. The present study showed that: (1) a significant amount of total variability of the behavioral indexes analyzed could be attributed to 24 h variation, (2) light/dark phases differences in EPM exploration were present at all developmental stages, (3) older Wistar rats explored less the EPM and were less active in their home cage compared with younger ones, and (4) behavioral indexes (EPM) decrease was phase related and partially related to a reorganization of rest-activity rhythm. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: circadian rhythm; elevated plus-maze; development; aging; anxiolysis; motor activity